Management of Vartma Sankoca (Ptosis) - A Case Study. - Nadang, Padma; Hiremath, Veerayya R; Shashikala , D K; Gururaj , N (International Research Journal of Ayurveda & Yoga, 2022)
Vartma sankocha is one among 80 nanatmaja vataja vikara, wherein patient is unable to open the eyelids. It can be compared to neurogenic type of acquired ptosis involving entire 3rd cranial nerve at any point in its path or rarely due to affection of branch supplying levator muscle. Treatment includes conservative management and surgical correction. In this case, 60year old male patient with history of drooping of right upper eyelid & intolerance to light since 1and1/2 year developed these complaints after hit of an insect to right upper eyelid. On tab Neostigmine from last one year but didn’t get much relief, hence visited our hospital for further treatment. Vatashamana chikitsa has been employed, Mukhabyanga with Kshirabala taila followed by Marsha Nasya with Karpasastyadi taila and dhumapana along with shamana chikitsa for 7 days. After 7 days of treatment there’s marked improvement in above said signs and symptoms.